2018
DOI: 10.1111/iej.12908
|View full text |Cite
|
Sign up to set email alerts
|

A 20‐year historical prospective cohort study of root canal treatments. A Multilevel analysis

Abstract: Root filled teeth were more frequently extracted for non-endodontic reasons rather than for endodontic disease. The majority of teeth with adequate root fillings, adequate restorations and included in a recall programme remained functional and healthy for more than 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 56 publications
3
44
0
1
Order By: Relevance
“…This finding is in agreement with Prati et al who found root fracture as the most frequent reason for the extraction of ETT in their 20year recall study. 30 Pirani et al found in their 10-year data for patients treated in a postgraduate endodontic program that loss of ETT is most frequently due to non-restorable fractures of tooth root structure. 29 This finding also suggests that a delay in the final coronal restoration, i.e., placement of a crown, could be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with Prati et al who found root fracture as the most frequent reason for the extraction of ETT in their 20year recall study. 30 Pirani et al found in their 10-year data for patients treated in a postgraduate endodontic program that loss of ETT is most frequently due to non-restorable fractures of tooth root structure. 29 This finding also suggests that a delay in the final coronal restoration, i.e., placement of a crown, could be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…29 Prati et al found 80% survival of ETT in their 20 years recall study with non-endodontic reasons as the main causes of the extraction of root-filled teeth. 30 Stenhagen et al recently studied the influence of coronal restorations on the survival of ETT and found that the indirect restorations have a significantly higher survival rate when compared to direct restorations. 31 In a largescale study conducted on the basis of insurance claims data, Yee et al concluded that long-term survival rates of initial root canal treatment are adversely affected by the delayed placement of the final coronal restoration.…”
Section: Introductionmentioning
confidence: 99%
“…In case of AP, extraction is also a possible treatment option. Although in Study III the reasons for extraction were unknown, previous studies report that root-filled teeth were extracted mainly on indications other than endodontic failure, such as being unrestorable due to caries and fractures, and also due to periodontal disease (47,64,65).…”
Section: Periapical Health Of Teeth With Direct Versus Indirect Restomentioning
confidence: 95%
“…The result should be a higher frequency of healthy periapical tissue in rootfilled teeth restored with crowns. However, in follow-up studies, no differences in success rates, in terms of periapical health, have been found with respect to composite, amalgam and crown restorations (32,46,47). On the other hand, one cross-sectional study disclosed a higher frequency of AP in root-filled teeth restored with composite than in those restored with crowns (55.7% and 34.3%, respectively) (48).…”
Section: Periapical Statusmentioning
confidence: 95%
See 1 more Smart Citation